The ratio of perirenal fat thickness to renal parenchymal thickness, a novel indicator of fat accumulation associated with kidney stones - Dekai Hu; Guoxiang Li; Defeng Ge; Leilei Ke; Hongmin Shu; Yang Chen; Zongyao Hao (Lipids in Health and Disease)
Abstract Background Metabolic syndrome, identified by increased visceral fat accumulation, is notably linked to a heightened risk of nephrolithiasis. Despite this, the influence of the perirenal fat thickness relative to renal parenchymal thickness on kidney stones (KS) development remains ambiguous. This study investigated the clinical characteristics of perirenal fat on both the left and right sides and explored the association between the aforementioned ratio and KS. Methods The study enrolled 161 participants who underwent computed tomography (CT) scans. In this study, kidneys were segregated into two categories based on the presence of stones: stone-bearing and non-stone-bearing for both the left and right kidneys. Perirenal fat parameters were extracted from the imaging workstation database. Both univariate and multivariate logistic regression analyses were conducted to explore the correlation between metrics related to perirenal fat and the occurrence of KS. Results Among the 161 participants, significant variations in perirenal fat were observed between the left and right kidneys, as well as between genders. Subsequent to adjustments for several confounding variables, the multivariable logistic regression model demonstrated a significant correlation between the ratio of perirenal fat thickness to renal parenchymal thickness and stone bearing kidney (P < 0.001). Conclusions The ratio of perirenal fat thickness to renal parenchymal thickness was significantly correlated with kidney stones.